(untitled) (International Journal of Education in Mathematics, Science and Technology, 2025)
This study delves into teacher candidates’ (TCs) perspectives, particularly in secondary mathematics and science education. Through qualitative analysis of survey data and essays from 17 TCs across two institutions, including 9 STEM education major TCs (math and science TCs), and 8 non-STEM TCs, diverse attitudes towards AI integration emerge. Our finding shows that more STEM TCs exhibit enthusiasm than non-STEM TCs. However, both groups emphasized the need for ethical AI use and students’ critical thinking skills. Their exposure to AI-embedded classroom experiences also showed differences. This study underscores the importance of tailored mathematics teacher education programs for AI integration in preparing future secondary teacher educators. In summary, this study not only sheds light on the perspectives of secondary TCs on AI integration but also provides actionable recommendations for enhancing teacher education programs to better prepare future educators for AI-enhanced classrooms.